Reprovação: efeitos do contexto escolar na trajetória dos alunos do ensino fundamental - Andre Augusto dos Anjos Couto (2017)
The academic trajectory of students at Fundamental Education constitutes, together with learning and school conditions, one of the dimensions of the right to Education. In order that this right is granted, the school must offer proper conditions that allow the student learning what is expected from her in each school stage and, thus, not being reproved and do not abandon the school before concluding Fundamental Education. The school constitutes a complex environment that suffers the influence of several intra and interschool factors, which can impact the performance and trajectory of the students. Therefore, it is significant that these factors be monitored in order to make sure that the right to education be attended. The present work is concentrated on the discussions on students trajectories an more specifically on grade repetition. The main objective is to investigate which school factors and students characteristics are related to grade repetition in Fundamental Education. The study concentrated on the Public State Education System of Minas Gerais, Brazil. The research was carried out in two complimentary stages: the first, of a quantitative nature, aimed at investigating by means of statistical techniques, which characteristics of the students and school factors are related to grade repetition. For this, were used data from contextual questionnaires from Prova Brasil [Brazil Exam] of 2013, and from the school indicators designed by Instituto Nacional de Estudos e Pesquisas Educationais Anísio Teixeira (INEP) [Anísio Texeira National Institute of Educational Studies and Researches]. Prova Brasil produced data from 183.354 students from the 9th Year of Fundamental Education of Public State Education System of Minas Gerais, and from 2,787 schools that offer the final years of the same Education System. The second stage, of a qualitative nature, consisted of the conduction of three focal groups, in which participated 30 students from the 9th Year of Fundamental Education, and an interview with a mathematics teacher that works at the same Education System and teaches for the 9th year students. The results evinced that the students characteristics such as lower socioeconomic level, gender (male), ethnical origin (black race), be worker and be provided with low family accompaniment predisposes the students to be reproved at school. The results also evinced that bigger and more complex schools, with a more rotary teacher staff favor the reprobation of the alumnus that study there. The results also pointed out differences between the relation of the grade repetition to the NSE of the students and the schools, which suggests the existence of intraschool segregation. Inefficient teaching-learning process, change of school, student absenteeism and indiscipline also contribute to grade repetition among the students of Fundamental Education.